AQUIFER OVEREXPLOITATION: WHAT DOES IT MEAN? - Custodio E. (My University, 2002)
Groundwater overexploitation and aquifer overexploitation are terms that are becoming common in water-resources management. Hydrologists, managers and journalists use them when talking about stressed aquifers or some groundwater conflict. Overexploitation may be defined as the situation in which, for some years, average aquifer abstraction rate is greater than, or close to the average recharge rate. But rate and extent of recharge areas are often very uncertain. Besides, they may be modified by human activities and aquifer development. In practice, however, an aquifer is often considered as overexploited when some persistent negative results of aquifer development are felt or perceived, such as a continuous water-level drawdown, progressive water-quality deterioration, increase of abstraction cost, or ecological damage. But negative results do not necessarily imply that abstraction is greater than recharge. They may be simply due to well interferences and the long transient period that follow changes in the aquifer water balance. Groundwater storage is depleted to some extent during the transient period after abstraction is increased. Its duration depends on aquifer size, specific storage and permeability. Which level of "aquifer overexploitation" is advisable or bearable, depends on the detailed and updated consideration of aquifer-development effects and the measures implemented for correction. This should not be the result of applying general rules based on some indirect data. Monitoring, sound aquifer knowledge, and calculation or modelling of behaviour are needed in the framework of a set of objectives and policies. They should be established by a management institution, with the involvement of groundwater stakeholders, and take into account the environmental and social constraints. Aquifer overexploitation, which often is perceived to be associated with something ethically bad, is not necessarily detrimental if it is not permanent. It may be a step towards sustainable development. Actually, the term aquifer overexploitation is mostly a qualifier that intends to point to a concern about the evolution of the aquifer-flow system in some specific, restricted points of view, but without a precise hydrodynamic meaning. Implementing groundwater management and protection measures needs quantitative appraisal of aquifer evolution and effects based on detailed multidisciplinary studies, which have to be supported by reliable data.
Keywords: GROUNDWATER MANAGEMENT; AQUIFER OVEREXPLOITATION; GROUNDWATER MINING; INTENSIVE AQUIFER DEVELOPMENT; SUSTAINABLE DEVELOPMENT